Electrical conductivity calculations in isochorically heated warm dense aluminum. (9th June 2017) - Sperling, P; Rosmej, S; Bredow, R; Fletcher, L B; Galtier, E; Gamboa, E J; Lee, H J; Reinholz, H; Röpke, G; Zastrau, U; Glenzer, S H
Abstract: We present a theoretical approach to derive the dc conductivity of warm dense matter (WDM) from x-ray Thomson scattering data. Predictions for the conductivity of aluminum at condensed matter densities are given within a wide temperature range ( 0.08 eV < k B T < 80 eV). Strong correlation effects are taken into account by ionic structure factors. Screening and Pauli blocking are described via a pseudopotential. The results are compared with other theoretical models and simulations as well as with experimental measurements in the liquid metal regime and recent experiments in the WDM regime.